Concerning Applied Significance of Career Theories (using the example of Gottfredson’s Theory of Circumscription and Compromise) (Journal of Educational Sciences, 2017)
The theory of circumscription and compromise of L. Gottfredson is one of the five most known theories of career development. In this theory the process of career development of a person from kindergarten until adolescence is described. As this process is described in details, the theory has great practical value. L. Gottfredson pays much attention to characteristics of career development of children of different age and makes recommendations on types of activities that are necessary at younger, middle and advanced school age for their successful career development. Besides, personal experience of pupils in getting acquainted with the world of professions is of great importance. It will allow students to avoid stereotypes and to choose a career in compliance with their interests and capabilities .Key words: career development, circumscription, compromise, self-concept, cognitive development.